A mullite etching route to tabular α-alumina crystals and application in adsorption desulfurization for dibenzothiophene. (15th March 2018) - Zhang, Ye; Liu, Dawei; Zhou, Ligong; Tang, Mingxing; Li, Xuekuan; Yang, Yongxing
Graphical abstract: SEM images of mullite-corundum composite, sol-gel -Al2 O3 and tabular -Al2 O3 . Highlights: Tabular α-Al2 O3 was synthesized by etching mullite from Six Aly Oz composites. The etching led to the formation of α-Al2 O3 with tabular morphology. Tabular α-Al2 O3 exhibited better DBT adsorption and easier regeneration. Abstract: Alpha-alumina (α-Al2 O3 ) materials has a wide range of applications because of its excellent properties at high temperature. Tabular α-Al2 O3 was unexpectedly synthesized by etching mullite from Six Aly Oz composites since our original intention was highly porous α-Al2 O3 . Silica-alumina xerogels with different Al/Si molar ratio as 3, 6, 9 and ∞ (pure alumina) were prepared via sol-gel route, followed by calcination at 1400 °C to obtain Six Aly Oz composites. XRD results showed that the composite existed as mullite when the Al/Si ratio equaled to 3 and as the combination of mullite and corundum (α-alumina) when the Al/Si ratio equaled to 6 and 9, while pure α-Al2 O3 was obtained when Al/Si ratio equaled to ∞ signed as sol-gel α-Al2 O3 . The mullite phase in Six Aly Oz composites could be etched completely by hydrofluoric acid under room temperature in terms of the treating time was long enough and left tabular α-Al2 O3 for the samples with Al/Si molar ratio as 6 and 9. The interaction between mullite and α-Al2 O3 during the thermo process may direct the formation of tabular morphology. Structural and property characterizations show the tabular morphology, low surface area, perfect crystallinity and weak acidity of α-Al2 O3 . Furthermore, the adsorption of dibenzothiophene, a molecular with planar morphology, on tabular α-Al2 O3, sol-gel α-Al2 O3 as well as γ-Al2 O3 was investigated at room temperature in comparison. Tabular α-Al2 O3 exhibited the highest adsorption capacity and best regeneration ability than other two.